Pendidikan Karakter: Solusi Bangsa Saat Ini - Adimin Diens (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Various problems that occur in this country have been taering human values. Multimdimensional crisis that never was completed, showed how vulnerable this nationâ€™s character. In this context â€œcharacter educationâ€ becomes a necessity to be reviewed. Character Learning in school tend recognition only the cognitive values with a little touch of understanding and appreciation of the affective value. Therefore, This paper in trying to provide an alternative how to implement character education to be able to internalized into the curriculum, learning at school, in family and society.